(untitled) (Zaporizhzhia Historical Review, 2021)
The difficult question of separating and resettlement of Nogay tribes from the South of Ukraine to the Kuban in the beginning of 1770-ies and the role of Zaporozhians in this process is being considered. It is shown that Cossacks-Nogay relationship was quite ambiguous.